2016
DOI: 10.18865/ed.26.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Migraine in the Northern Manhattan Study

Abstract: Conclusion:Hypertension, particularly uncontrolled and of long duration, is associated with migraine, both with and without aura, in a predominantly Hispanic community-based cohort. Ethn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
(35 reference statements)
5
31
3
2
Order By: Relevance
“…We found hypertension to be significantly associated with MH, consistent with multiple studies [3, 22, 23] including one based on self-report [24]. The North Manhattan Study found an association of hypertension with migraine [23]; however, their population was predominantly Hispanic and older than our population.…”
Section: Discussionsupporting
confidence: 89%
“…We found hypertension to be significantly associated with MH, consistent with multiple studies [3, 22, 23] including one based on self-report [24]. The North Manhattan Study found an association of hypertension with migraine [23]; however, their population was predominantly Hispanic and older than our population.…”
Section: Discussionsupporting
confidence: 89%
“…For example available evidence reported that the odds of migraine is increased in obese individuals (15,48). Moreover, although there is controversial evidence regarding the association between hypertension and migraine, several ndings delineated that long duration and uncontrolled hypertension, especially systolic blood pressure, may have a positive link with migraine with/without aura (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Gardener и соавт. [31] представили результаты многоцентрового популяционного исследования NOMAS (The Northern Manhattan Study), в котором приняли участие 1338 человек (средний возраст 68,1±9, 6 лет, 80% пациентов без мигрени, 6% с мигренью с аурой и 15% -с мигренью без ауры). АГ имела место у 76% обследуемых, длительность заболевания была различной, также были включены пациенты как с контролируемой АГ (достигнуты целевые уровни АД), так и с неконтролируемой АГ.…”
Section: взаимосвязь между мигренью и агunclassified
“…К основным патогенетическим механизмам и мигрени, и АГ относится также гиперсимпатикотония, что также объясняет взаимосвязь между этими двумя заболеваниями [31]. Косвенным подтверждением этой гипотезы является эффективность бета-адреноблокаторов (пропранолола, метопролола) в профилактике приступов мигрени, которые снижают симпатический тонус за счет блокады бета-адренорецепторов [39].…”
Section: взаимосвязь между мигренью и агunclassified